English as a Second language in 350 YouTube Videos: A Big Data Analysis - Kang, Namkil (Advances in Social Sciences Research Journal, 2023)
The ultimate goal of this paper is to provide an in-depth analysis of 350 YouTube videos broadcasted about English as a second language. A point to note is that one noun obtains the highest frequency (1,439 tokens) in 350 YouTube videos. A further point to note is that topic 9 was the most occurred one, followed by topic 7, topic 10, and topic 16, in descending order. A major point of this paper is that the keyword English is the most important and pivotal in the word cloud of 350 YouTube videos, followed by the keyword language, and the keyword person, in that order. When it comes to the use of core keywords, the keyword English was the most frequently used in 350 YouTube videos, followed by the keyword language, the keyword video, the keyword paper, and the keyword com, in that order. This paper also argues that the keyword English obtains the highest centrality and frequency and the keyword language follows. When it comes to the keyword SSLC, its centrality is high (the third highest), but its frequency is relatively low. The so-called frequency and centrality both refer to the degree of the importance of words, but they are different in that the former refers to the use of words, whereas the latter refers to the importance, prominence, prestige, influence, and reputation of words.